2012
DOI: 10.1002/ibd.21872
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Reserve in Young Women of Reproductive Age with Crohnʼs Disease

Abstract: Women with CD do not have severe ovarian reserve alterations compared to a control population. However, age ≥ 30 years and a colonic location of the disease could be associated with an accelerated loss of follicles. These data could encourage gastroenterologists to inform CD women of the risk of delaying childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 42 publications
1
52
0
1
Order By: Relevance
“…Elevated levels of TNF-α in the follicular fluid were correlated with poor oocyte quality (44), and Winger et al (45) showed that TNF-α blockage improves IVF outcomes in young infertile women. Recent studies show that patients with endometriosis and Crohn disease have significantly lower AMH levels compared with healthy controls, supporting the hypothesis that uncontrolled inflammation adversely affects the ovarian reserve (27,28). Previous studies suggested that IL-1 hinders hormonal regulation within the ovary (46,47).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Elevated levels of TNF-α in the follicular fluid were correlated with poor oocyte quality (44), and Winger et al (45) showed that TNF-α blockage improves IVF outcomes in young infertile women. Recent studies show that patients with endometriosis and Crohn disease have significantly lower AMH levels compared with healthy controls, supporting the hypothesis that uncontrolled inflammation adversely affects the ovarian reserve (27,28). Previous studies suggested that IL-1 hinders hormonal regulation within the ovary (46,47).…”
Section: Discussionmentioning
confidence: 81%
“…In the male, high levels of IL-1 in the testis, as observed in IL-1 receptor antagonistdeficient mice, impair sperm quality and its ability to fertilize oocytes (26). Recent studies suggest that inflammatory conditions may affect ovarian reserve in women (27,28). However, to the best of our knowledge, the possible involvement of inflammatory pathways and the role of IL-1 in the age-related exhaustion of ovarian reserve have never been directly approached.…”
Section: Significancementioning
confidence: 99%
“…When oocytes are exposed to an aged ovarian microenvironment, they themselves will undergo a process of reproductive aging (Tatone et al ., ). Inflammatory cytokines constitute one of the most potent factors in the ovarian microenvironment that are involved in physiologic and pathologic processes within the ovary (Boots & Jungheim, ), and recent studies have shown effects of inflammatory conditions on ovarian reserve in women (Freour et al ., ). Elevated levels of pro‐inflammatory factors, including IL‐1β and TNF‐α (tumor necrosis factor‐a), have been reported to be associated with poor oocyte quality and negative effects on IVF outcomes (Lee et al ., ; Revelli et al ., ; Winger et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Former studies have found a considerable reduction in postoperative fertility in women with UC requiring ileoanal pouch anastomosis (IPAA),9–12 and after CD surgery 13 14. Excluding voluntary childlessness, additional causes of infertility may include increased disease activity and low ovarian reserve 13 15 16. Serum anti-Mullerian hormone, an indicator of ovarian reserve, is lower in women with CD, especially during periods of active disease, compared with healthy controls 15 16…”
Section: Introductionmentioning
confidence: 99%